Epidemiology of musculoskeletal injury in the tennis player. Issue 7 (3rd May 2012) - Abrams, Geoffrey D; Renstrom, Per A; Safran, Marc R
Abstract : Tennis is a popular sport with tens of millions of players participating worldwide. This popularity was one factor leading to the reappearance of tennis as a medal sport at the 1988 Summer Olympics in Seoul, South Korea. The volume of play, combined with the physical demands of the sports, can lead to injuries of the musculoskeletal system. Overall, injury incidence and prevalence in tennis has been reported in a number of investigations. The sport creates specific demands on the musculoskeletal system, with acute injuries, such as ankle sprains, being more frequent in the lower extremity while chronic overuse injuries, such as lateral epicondylitis, are more common in the upper extremity in the recreational player and shoulder pain more common in the high-level player. This review discusses the epidemiology of injuries frequently experienced in tennis players and examines some of these injuries' correlation with the development of osteoarthritis. In addition, player-specific factors, such as age, sex, volume of play, skill level, racquet properties and grip positions as well as the effect of playing surface on the incidence and prevalence of injury is reported. Finally, recommendations on standardisation of future epidemiological studies on tennis injuries are made in order to be able to more easily compare results of future investigations.